2021
DOI: 10.2196/28413
|View full text |Cite
|
Sign up to set email alerts
|

Use of Machine Learning Algorithms to Predict the Understandability of Health Education Materials: Development and Evaluation Study

Abstract: Background Improving the understandability of health information can significantly increase the cost-effectiveness and efficiency of health education programs for vulnerable populations. There is a pressing need to develop clinically informed computerized tools to enable rapid, reliable assessment of the linguistic understandability of specialized health and medical education resources. This paper fills a critical gap in current patient-oriented health resource development, which requires reliable … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Mobile Information Systems increasing teaching quality. e work of [14,15] attempts to incorporate globally recognized clinical recommendations into machine learning algorithms to help foreign students in Australian institutions evaluate health resources. Inspired from the above, this paper provides a deep learning-based college English education evaluation method for successfully improving the effect of English teaching evaluation.…”
Section: Related Workmentioning
confidence: 99%
“…Mobile Information Systems increasing teaching quality. e work of [14,15] attempts to incorporate globally recognized clinical recommendations into machine learning algorithms to help foreign students in Australian institutions evaluate health resources. Inspired from the above, this paper provides a deep learning-based college English education evaluation method for successfully improving the effect of English teaching evaluation.…”
Section: Related Workmentioning
confidence: 99%
“…The importance of these other criteria is supported by recent machine learning algorithms that predict the accessibility of health information. For example, these studies have shown that text features such as familiarity with the text's vocabulary and cohesion across sentences may also play an important role [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, the study of the quality of language for effective health communication and education has focused on the complexity of health and medical educational resources [ 1 - 5 ]. A range of readability assessment tools have been developed to measure the lexical, grammatical, and syntactic features of health and educational resources [ 6 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural language processing tools and machine learning algorithms have gained increasing popularity in health informatics. These flexible and versatile computational techniques can achieve high-precision prediction of outcomes based on the data-driven learning and computing of quantifiable features of the study object [ 1 , 7 , 10 , 20 ]. This represents a significant advance from statistics, which requires the presence of both dependent and independent variables to fit their relations into developed statistical models [ 21 ].…”
Section: Introductionmentioning
confidence: 99%